Hubungan Implementasi Hukum Terhadap Dampak Psikis Mahasiswa Korban Bullying di Fakultas Hukum UPN “Veteran” Jakarta - Oktaviani, Eka Putri; Wiliananda, Dwi Cinta; Khalila, Khalisa Putri; Khairiyyah, Lina Husnul (Media Hukum Indonesia (MHI), 2024)
Bullying is an action or behavior carried out by means of physical, verbal or emotional/psychological harm by a person or group who feels physically or mentally weaker repeatedly without any resistance with the aim of making the victim suffer. This research aims to: (1) describe the impact of bullying on students' mental health, (2) determine the forms of bullying that occur within the UPN Veteran Jakarta Faculty of Law, (3) identify actions that can be taken to address bullying problems. The approach taken in this research is quantitative using a questionnaire instrument technique via Google Form to obtain research data. From this research it was found that: (1) the impact that arises from bullying behavior on students at the Faculty of Law, UPN Veteran Jakarta, is that the victim becomes less confident and feels restless or nervous when meeting with large groups of people; (2) the form of bullying that occurs within the Faculty of Law at UPN Veteran Jakarta is cyberbullying, namely by the victim's friends uploading photos of the victim on social media without permission, apart from that there is also verbal bullying, namely by mocking or commenting on ethnicity and/or race and/ or religion; (3) the action that can be taken to address bullying problems is through criminal acts.